Analisis Citra Politik Pasangan Calon Gubernur Jakarta dalam Pemenangan Pilkada 2024 - Hanifah Islamiyah; Umaiyah, Siti (UIN Raden Mas Said Surakarta, 2025)
The 2024 Jakarta Regional Election (Pilkada) was marked by intense competition. One gubernatorial candidate pair, supported by only two political parties, emerged victorious over a rival pair backed by 16 parties. Another candidate pair also contested the election independently. The candidates competed fiercely to build strong political branding—not only through traditional campaigns but also by utilizing social media platforms such as Instagram and YouTube. This descriptive research explores how the candidate pairs developed their political branding and why it contributed to electoral success. Findings reveal that each pair shaped their brand based on personality, competencies, values, and the public image they intended to project. The winning pair, Pramono Anung and Rano Karno, owed their success to effective branding strategies involving self-identification, political product development, and strategic positioning. Their strong and consistent branding approach helped them connect with voters and ultimately secure victory in the 2024 Jakarta Pilkada.